“Sustainable security” through river enlargements: A political ecology of nature-based solutions and flood control in the Rhone Valley, Switzerland - Alexis Metzger; René Véron (Développement Durable et Territoires)
The largest ongoing river training project in Switzerland, the so-called Third Correction of the Rhone in the Valais, builds on nature-based solutions (river enlargements and renaturation) while official documents and discourses also refer to an ill-defined notion of “sustainable security” and the goal of controlling floods. Drawing on qualitative data from stakeholder interviews and analysis of official documents, this paper examines the concept of sustainable security, as it is applied to the river project in terms of a balance between security and environmental concerns, the relationship between the three pillars of sustainability, and the opportunities of the population to debate the spatial development of the Rhone Valley. We argue that legal provisions, the dominance of security concerns and technocratic framings of the project foreclose more substantive political debate on the sustainable future of the hydrosocial territory of the Rhone Valley.